Anthriscifolcine A, a C18-diterpenoid alkaloid - Zhi-Jun Song (Acta Crystallographica Section E, 2011)
The title compound, C26H39NO7, which was isolated from Delphinium anthriscifolium var. majus, has a lycoctonine carbon skeleton containing four six-membered rings (A, B, D and E) and three five-membered rings (C, F and G). Rings A, B and E adopt chair conformation, while ring D adopts a boat conformation. Rings C and F adopt envelope conformations.